2014
DOI: 10.1080/09243046.2014.898436
|View full text |Cite
|
Sign up to set email alerts
|

Electrostriction study for single-walled carbon nanotubes-based composite

Abstract: This paper proposes a 3D finite element method procedure to study the electrostrictive property of the single-walled carbon nanotube (SWCNT)-based composite. The numerical model in nanoscale is developed to investigate the electrostrictive behavior of the SWCNT and the polyvinylidene fluoride and trifluoroethylene P(VDF-TrFE) composite. A bond electrical contact model is adopted to reproduce the coupled electromechanical effects of the interface between SWCNT and P(VDP-TrFE). According to the model proposed, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Tang et al 5 proposed a finite element method procedure to study the electrostrictive property of the carbon nanotube composite. They showed that the electrostriction of the composite was greatly depend on their alignment in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al 5 proposed a finite element method procedure to study the electrostrictive property of the carbon nanotube composite. They showed that the electrostriction of the composite was greatly depend on their alignment in the matrix.…”
Section: Introductionmentioning
confidence: 99%